A Childhood Cut Short: Child Deaths in Penal Custody and the Pains of Child Imprisonment. Issue 3 (6th September 2016) - GOOCH, KATE
Abstract: The death of a child in penal custody is an infrequent, but particularly tragic, event. In seeking to explain such events, the tendency has been to focus on individual pathology or vulnerability. This article begins from the premise that in order to better understand child deaths in penal custody, it is necessary to move beyond such explanations and consider the wider systematic, cultural, operational, and policy issues. It contributes to the debate by exploring the specific 'pains of child imprisonment' as narrated by teenage boys (aged 15–17 years) in an English young offender institution (YOI). It is argued that, trapped in 'kidulthood', the dual status of child prisoners poses experiential, conceptual, and practical complexities, but it also produces pains, losses, and burdens that are unique to childhood.